Religion's Role in a Martian War of Independence. Issue 2 (20th June 2022) - Rappaport, Margaret Boone; Corbally, Christopher J.
Abstract: Astrotheologians and Astroethicists must be futurists at the same time that they articulate theological issues and moral quandaries in future settlement programs. One methodology used to recommend solutions is the construction of a scenario, a story that extrapolates from what is known to what is yet unknown, following models in international planning and operations research. In anticipation of the roles of religion and the clergy in an off‐Earth settlement on Mars, we offer this dramatic story, which takes place during a long, 10‐year Martian War of Independence. Issues framed on Earth (as in the 1962 UN Principles) take on new importance in a multi‐national, multi‐ethic, Martian society, where political and religious leadership based essentially on future versions of ancient Judeo‐Christian principles is key to survival.